Hubble Frontier Field photometric catalogues of Abell 370 and RXC J2248.7−4431: multiwavelength photometry, photometric redshifts, and stellar properties. Issue 1 (19th August 2019) - Bradač, Maruša; Huang, Kuang-Han; Fontana, Adriano; Castellano, Marco; Merlin, Emiliano; Amorín, Ricardo; Hoag, Austin; Strait, Victoria; Santini, Paola; Ryan, Russell E; Casertano, Stefano; Lemaux, Brian C; et al.
ABSTRACT: This paper presents multiwavelength photometric catalogues of the last two Hubble Frontier Fields (HFFs), the massive galaxy clusters Abell 370 and RXC J2248.7−4431. The photometry ranges from imaging performed on the Hubble Space Telescope to ground-based Very Large Telescope and Spitzer /Infrared Array Camera, in collaboration with the ASTRODEEP team, and using the ASTRODEEP pipeline. While the main purpose of this paper is to release the catalogues, we also perform, as a proof of concept, a brief analysis of z > 6 objects selected using dropout method, as well as spectroscopically confirmed sources and multiple images in both clusters. While dropout methods yield a sample of high- z galaxies, the addition of longer wavelength data reveals that as expected the samples have substantial contamination at the ∼30–45 per cent level by dusty galaxies at lower redshifts. Furthermore, we show that spectroscopic redshifts are still required to unambiguously determine redshifts of multiply imaged systems. Finally, the now publicly available ASTRODEEP catalogues were combined for all HFFs and used to explore stellar properties of a large sample of 20 000 galaxies across a large photometric redshift range. The powerful magnification provided by the HFF clusters allows for an exploration of the properties of galaxies with intrinsic stellar masses as low as M * ≳ 10 7 M⊙ and intrinsic star formation rates ∼0.1–1 M⊙ yr −1 at z > 6.